Poverty Pressure for People with Social Welfare Problems (PMKS) During the Pandemic in Gresik Regency - Ratna Azis Prasetyo; Septi Ariadi; Bagong Suyanto; Sudarso Sudarso; Abd Hannan; Risca Yunike Putri (Faculty of Social Science, Universitas Negeri Malang, 2022)
The COVID-19 pandemic has brought a domino effect to increase poverty rates. In Gresik Regency, the number of layoffs (PHK) and small businesses that went out of business added new poor people so the number of PMKS increased. This study intends to describe the poverty pressure experienced by PMKS during the COVID-19 pandemic and the appropriate handling strategy. The research method used is descriptive research by conducting structured interviews to 400 PMKS in Gresik Regency. The results of this study found that the poverty pressure carried out by PMKS during the COVID-19 pandemic was a reduction in savings and assets owned to meet their daily needs during the pandemic where they lost their jobs and the businesses they were engaged in experienced setbacks, difficulties in meeting the needs of life and family nutrition, increased debt to domestic disputes and the threat of children dropping out of school. The easiest survival strategy for PMKS is to make changes to consumption patterns, while help from relatives is relatively difficult to obtain and productive activities such as business diversification are also relatively difficult to do. The coping strategy that can be done is to empower PMKS, especially the productive age group, which aims not only to prevent the fading of PMKS' ability to help themselves but in the long term they can get out of the pressures of poverty they are experiencing.